Adaptive Headlight System for accident prevention - Shreyas, S.; Raghuraman, Kirthanaa; Padmavathy, A. P.; Prasad, S. Arun; Devaradjane, G. (2014 International Conference on Recent Trends in Information Technology, 2014)
This paper focuses on the design and working of a microcontroller based Adaptive Headlight System (AHS) for automobiles. The main purpose of this system is to present a cost effective technique to illuminate blind spots while driving in the night and during the times when the visibility is reduced significantly so as to make the objects visible in those darkened locations and thereby prevent accidents. The system functions in accordance to the controlled input from Atmel AT89S52 microcontroller unit which drives the stepper motors connected to the headlights. The system is also designed to receive input from the indicator switch wherein a full turn is achieved by the headlight mirror when the indicator input is given. Also, the adaptive headlights are automatically switched on when the amount of light measured by a photo diode falls below a threshold, thereby eliminating the need for the driver to switch on the headlights.